Original paperEffect of bladder distension on dosimetry of organs at risk in computer tomography based planning of high-dose-rate intracavitary brachytherapy for cervical cancer - Patra, Niladri B.; Manir, Kazi S.; Basu, Swapnendu; Goswami, Jyotirup; Kabasi, Apurba K.; Sarkar, Shyamal K. (Journal of Contemporary Brachytherapy, 2013)
Purpose : Distension and shape of urinary bladder may vary during intracavitary brachytherapy (ICBT) for cervical cancer, significantly affecting doses to bladder, rectum , sigmoid colon and small intestine and consequently late radiation toxicities. This study is to evaluate the effects of different fixed volume bladder distention on dosimetry, assessed by three dimensional image based planning, in different organs at risk during the treatment of cervical cancer with ICBT. Material and methods : Forty seven cervical cancer patients (stage IB to IVA) were qualified for ICBT following external beam radiotherapy. Urinary bladder was distended with different volumes of normal saline instilled by a Foley’s catheter. Planning CT scans were performed after insertion of applicators and three dimensional treatment planning was done on Brachyvision ® treatment planning system (Varian Medical Systems, Palo Alto, CA). Dose volume histograms were analyzed. Bladder, rectum, sigmoid colon and small intestine doses were collected for individual plans and compared, based on the amount of bladder filling. Results: Mean dose to the bladder significantly decreased with increased bladder filling. However, doses to the small volumes (0.1 cc, 1 cc, 2 cc) which are relevant for brachytherapy, did not change significantly with bladder filling for bladder, rectum or sigmoid colon. Nevertheless, all dose values of small intestine are decreased significantly with bladder filling. Conclusions : Bladder distension has no significant effect on doses received during brachytherapy by relevant volumes of bladder, rectum and sigmoid colon except intestine where values are decreased with bladder distension. A larger study with clinical correlation of late toxicities is essential for proper evaluation of this strategy.